Nutritious Eating Program from the Perspective of Economic Justice - Rahmat Kurniawan (PROFJES: Profetik Jurnal Ekonomi Syariah, 2026)
The presence of the Free Nutritious Meal program is based on the government’s vision aligned with the fifth principle of Pancasila, namely social justice for all Indonesian people. However, in practice, there are still instances of injustice, such as corruption, collusion, and nepotism (KKN) in the recruitment of SPPG personnel, violations in food distribution regulations, and limited partnerships with MSMEs/street vendors, which result in revenue decline. This study is qualitative research with a descriptive approach. The findings of the study indicate that the free nutritious meal program, when viewed from the perspective of economic justice, can be realized by implementing distributive justice and structural justice. Distributive justice ensures that all Indonesian citizens have equal opportunities, both to become part of the MBG implementation team, referred to as the Nutritional Fulfillment Service Unit (SPPG), and to enjoy the facilities of free nutritious meals. Structural justice, on the other hand, ensures that any unlawful actions related to the recruitment of SPPG personnel or other violations are addressed accordingly. The distribution of free nutritious food must be immediately enforced firmly without discrimination. Keywords: Free Nutritious Food Program, Justice, Economy.